Simulation Optimization of a Four-Stage Supply Chain System - Saif, A.-W.A.Seliaman (2006)
Today's information technology allows firms to share inventory profiles and demand data quickly and inexpensively. In this paper we develop a discrete-event simulation model for a four-stage supply chain. We assume that the four chain parties share their inventory and demand information. The performance measure that is used in the model to evaluate the system performance is expected total cost which consists of the inventory holding cost, the ordering cost, and the shortage cost. The simulation model is optimized using SimRunner optimization package.